Master your next move - Watkins, Michael (Harvard Business Press, 2019)
Master Your Next Move answers a distinct need, focusing on the most common types of transitions leaders face and the unique challenges posed by each. Based on years of research, and now with a new introduction, this indispensable book explores eight crucial transitions virtually everyone encounters during their career, including promotion, leading former peers, onboarding into a new company, making an international move, and turning around a business in crisis